AN EMBEDDING THEOREM FOR A CLASS OF CONVEX SETS IN NONARCHIMEDEAN NORMED SPACES - Aghajani, M.; Nourouzi, K. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
In this article we show that the class of all compact convex sets of a real nonarchimedean normed space can be embedded in a real nonarchimedean normed space.